Answer:
x = - 8
y = - 48
Explanation:
Here, y = 3x - 24 and 5x - y = 8 is given
So, First name the equation
y = 3x - 24 ...(1)
5x - y = 8 ...(2)
Now, Put the value of y in equation (2) we get
5x - y = 8
5x - (3x - 24) = 8
5x - 3x + 24 = 8
2x = 8 - 24
2x = -16
x = -16÷2
x = - 8
Here, we get the value of x in equation (1)
y = 3x - 24
y = 3(- 8) - 24
y = - 24 - 24
y = - 48
FOR VERIFICATION ONLY:
y = 3x - 24
-48 = 3(-8) - 24
-48 = -48
5x - y = 8
5(-8) -(- 48) = 8
-40 + 48 = 8
8 = 8
Hence, L.H.S = R.H.S
-TheUnknownScientist